Sponge body solid electrolyte and preparation method and application thereof

By using three-dimensional "cavern" materials to adsorb electrolyte in solid-state batteries, the interface problems between the electrolyte and electrode are solved, the battery performance and stability are improved, and the scope of application of solid-state electrolytes is expanded.

CN119852508AActive Publication Date: 2025-04-18XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510119176.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-18
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

In the existing solid-state battery technology, the interface problem between the electrolyte and the electrode is difficult to effectively solve, resulting in poor battery performance and sulfide solid electrolyte is only effective under large pressures.

Method used

By attaching three-dimensional "cavern" material to the surface of the solid electrolyte membrane, the electrolyte is adsorbed, so that the electrolyte exudes under a smaller pressure, improving the interface contact between the electrolyte and the electrode.

Benefits of technology

The interface problem between the electrolyte and the electrode is solved, the performance and stability of the battery are improved, the adverse effects on the electrolyte performance are avoided, and the scope of application of sulfide solid electrolyte is expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852508A_ABST
    Figure CN119852508A_ABST
Patent Text Reader

Abstract

The invention provides a'sponge 'solid electrolyte and a preparation method and application thereof, and relates to the technical field of solid-state batteries, the'sponge' solid electrolyte comprises a solid electrolyte and saturated'sponge 'materials covering two sides of the solid electrolyte; wherein the saturated'sponge body 'material is obtained by absorbing electrolyte by the'sponge body' material with a porous structure until the'sponge body 'material is in a saturated state; and the saturated sponge body material can generate elastic deformation under the action of certain pressure, so that the electrolyte seeps out of the sponge body material. According to the invention, the three-dimensional sponge body material is additionally arranged on the surface of the solid electrolyte membrane to adsorb the electrolyte, and the electrolyte seeps out under a relatively small pressure, so that the interface problem between the electrolyte and an electrode is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a "sponge" solid-state electrolyte and a preparation method and application thereof. Background Art

[0002] In solid-state batteries, solid electrolyte membranes play a vital role. At present, in the prior art, commonly used inorganic solid electrolytes include sulfide solid electrolytes, perovskite solid electrolytes, halide solid electrolytes, etc. Among them, sulfide solid electrolyte membranes have high ionic conductivity and can meet the basic performance of battery design. However, the interface problem is a long-standing problem that has plagued the development of solid-state battery technology, mainly due to poor contact between the electrolyte and the electrode and side reactions at the interface. The solution of the prior art is mainly to improve the interface contact between the solid electrolyte membrane and the electrode through various additives, such as surfactants, binders, etc. to increase the contact area and adhesion between the electrolyte and the electrode, and reduce the side reactions at the interface by coating a protective layer on the electrode surface. Although the above solutions have improved the interface problem between the electrolyte and the electrode to a certain extent, there are still some problems and limitations. First, the composition and structure of the additives are very complex and changeable. It is very difficult to select suitable additives to effectively solve the interface problem, and the additional additives usually have an adverse effect on the performance of the battery. In addition, although coating a protective film layer on the electrode surface can reduce the side reactions at the interface, it will significantly increase the resistance of the electrode, which increases the internal polarization impedance of the battery. Moreover, sulfide solid electrolytes can only work under higher pressure (≥5MPa), which limits their usage scenarios.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The purpose of the present invention is to provide a "sponge" solid electrolyte and its preparation method and application. The present invention solves the interface problem between the electrolyte and the electrode by adding a three-dimensional "sponge" material on the surface of the solid electrolyte membrane to adsorb the electrolyte, allowing the electrolyte to seep out under a relatively low pressure.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a "sponge" solid electrolyte, comprising a solid electrolyte and a saturated "sponge" material covering both sides of the solid electrolyte;

[0007] Wherein, the saturated "sponge" material is obtained by absorbing the electrolyte to a saturated state through the "sponge" material having a porous structure;

[0008] The saturated "sponge" material can undergo elastic deformation under a certain pressure, so that the electrolyte seeps out of the "sponge" material.

[0009] Further, based on the above technical solution, the thickness of the "sponge" material with a porous structure is 5 to 200 μm, preferably 25 μm;

[0010] And / or, the porosity of the "sponge" material having a porous structure is 15% to 70%, preferably 40%;

[0011] And / or, the pressure applied to the saturated "sponge" is in the range of 0.2 to 2 MPa, preferably 0.4 MPa.

[0012] Further, on the basis of the above technical solution, the "sponge" material with a porous structure includes one of polyurethane sponge, polyimide sponge, nickel foam or aluminum foam;

[0013] And / or, the solid electrolyte is an inorganic solid electrolyte;

[0014] The inorganic solid electrolyte is a sulfide solid electrolyte;

[0015] The sulfide solid electrolyte is LiPSCl5.

[0016] Further, on the basis of the above technical solution, the electrolyte is an organic lithium salt electrolyte;

[0017] The organic lithium salt electrolyte comprises an organic lithium salt and a solvent;

[0018] The concentration of the organic lithium salt electrolyte is greater than 1 mol / L;

[0019] The organic lithium salts include N-methyl-N-butylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, bis(trifluoromethanesulfonyl)imide lithium, lithium trifluoromethanesulfonate, and lithium tris(trifluoromethylsulfonyl)imide;

[0020] The solvent includes one or more of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.

[0021] Furthermore, based on the above technical solution, the saturated state refers to a state in which the "sponge" material with a porous structure can no longer absorb the electrolyte.

[0022] The present invention also provides a method for preparing the above-mentioned "sponge" solid electrolyte, comprising the following steps:

[0023] S1: pre-treating the "sponge" material with a porous structure;

[0024] S2: Soaking the pretreated "sponge" material in an electrolyte until it is saturated to obtain a saturated "sponge" material;

[0025] S3: Cover the saturated "sponge" material on both sides of the solid electrolyte to obtain a "sponge" solid electrolyte.

[0026] Further, based on the above technical solution, in step S1, the pretreatment includes selecting the porosity and thickness of the "sponge" material with a porous structure, and cutting it into the same size as the solid electrolyte.

[0027] The present invention also provides a "sponge" solid electrolyte prepared by the preparation method of the "sponge" solid electrolyte as described above or an application of the "sponge" solid electrolyte as described above, which can be used to be assembled with positive and negative electrode sheets in a solid-state battery mold to form a solid-state battery.

[0028] Further, on the basis of the above technical solution, in the solid-state battery, from top to bottom, respectively: negative electrode current collector, negative electrode active material layer, saturated "sponge" material layer, inorganic solid electrolyte layer, saturated "sponge" material layer, positive electrode active material layer and positive electrode current collector;

[0029] Wherein, the negative electrode current collector and the negative electrode active material layer coated on the surface of the negative electrode current collector constitute the negative electrode sheet;

[0030] The positive electrode current collector and the positive electrode active material layer coated on the surface of the positive electrode current collector constitute a positive electrode sheet;

[0031] The inorganic solid electrolyte layer and the saturated "sponge" material layers on both sides of the inorganic solid electrolyte layer constitute a "sponge" solid electrolyte.

[0032] Further, based on the above technical solution, the positive electrode current collector includes aluminum foil or carbon material;

[0033] The positive electrode active material layer is a high-nickel NCM ternary material;

[0034] And / or, the negative electrode current collector comprises one of copper foil, titanium foil, nickel foil and stainless steel;

[0035] The negative electrode active material layer is made of silicon-carbon material.

[0036] The present invention provides a "sponge" solid electrolyte and its preparation method and application, and the beneficial effects are as follows:

[0037] 1. Improved interface contact: The present invention solves the interface problem between the electrolyte and the electrode by attaching a three-dimensional "sponge" material on the surface of the solid electrolyte membrane to absorb the electrolyte, allowing the electrolyte to seep out under a relatively low pressure. Compared with the prior art of improving the interface contact between the electrolyte and the electrode by adding various additives, the present invention does not require additives, thus avoiding adverse effects on the electrochemical properties of the electrolyte, and also does not require optimization of the composition and structure of the electrolyte, thus saving experimental research and development costs.

[0038] 2. High stability: The "sponge" material in the present invention is stable at both high and low voltages, avoiding contact between sulfide and the positive and negative electrodes and reducing side reactions at the interface. Compared with the prior art of reducing side reactions at the interface by coating a protective film on the electrode surface, the "sponge" material of the present invention can not only reduce side reactions at the interface, but also, due to its high stability, can be used in a wider voltage range, thereby improving the stability and service life of the battery.

[0039] 3. Electrolyte seepage: The present invention allows the electrolyte to seep out of the "sponge" material under relatively low pressure, thus ensuring sufficient contact between the electrolyte and the electrode. Compared with the prior art which improves the compatibility of the electrolyte with the electrode by optimizing the composition and structure of the electrolyte, the present invention allows the electrolyte to seep out by physical means, which is simple to operate, highly efficient, and can significantly improve the performance of the battery.

[0040] 4. Low cost: The "sponge" material used in the present invention is low in cost, easy to obtain and prepare. Compared with the prior art which requires a lot of experimental research and development costs to optimize the composition and structure of the electrolyte, the present technical solution has obvious cost advantages. Compared with the prior art, the present invention not only has significant advantages in solving the interface problem between the electrolyte and the electrode, but also has outstanding advantages in terms of stability, electrolyte leakage and cost.

[0041] 5. The present invention can make the electrolyte seep out of the "sponge" material under relatively low pressure, thus overcoming the limitation that sulfide solid electrolytes can only work under relatively high pressure, and expanding the application scope of sulfide solid electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 A schematic diagram of the structure of the mold battery provided by the present invention;

[0044] Figure Number:

[0045] 1. Negative electrode current collector; 2. Negative electrode active material layer; 3. Saturated "sponge" material layer; 4. Inorganic solid electrolyte layer; 5. Positive electrode active material layer; 6. Positive electrode current collector. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0047] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0048] According to a first aspect of the present invention, there is provided a "sponge" solid electrolyte, comprising a solid electrolyte and a saturated "sponge" material covering both sides of the solid electrolyte;

[0049] Wherein, the saturated "sponge" material is obtained by absorbing the electrolyte to a saturated state through the "sponge" material having a porous structure;

[0050] The saturated "sponge" material can undergo elastic deformation under a certain pressure, so that the electrolyte seeps out of the "sponge" material.

[0051] Specifically, the present invention causes the electrolyte to seep out from the "sponge" material under pressure, ensuring sufficient contact between the electrolyte and the electrode. Compared with the prior art that improves the compatibility of the electrolyte with the electrode by optimizing the composition and structure of the electrolyte, the present technical solution causes the electrolyte to seep out by physical means, which is simple to operate, highly efficient, and can significantly improve the performance of the battery.

[0052] As an optional embodiment of the present invention, the thickness of the "sponge" material with a porous structure is 5 to 200 μm (for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, etc.), preferably 25 μm;

[0053] The porosity of the "sponge" material with a porous structure is 15% to 70% (such as 20%, 30%, 40%, 45%, 50%, 55%, 60%, 65%, etc.), preferably 40%;

[0054] The pressure applied to the saturated "sponge" is in the range of 0.2 to 2 MPa (such as 0.4 MPa, 0.6 MPa, 0.8 MPa, 1.0 MPa, 1.2 MPa, 1.4 MPa, 1.6 MPa, 1.8 MPa, etc.), preferably 0.4 MPa.

[0055] Specifically, by attaching a three-dimensional saturated "sponge" material to the surface of an inorganic solid electrolyte, the electrolyte can be exuded under pressure, thereby improving the contact between the electrolyte and the electrode. The "sponge" material with a porous structure is stable at both high and low voltages. Attaching it to the surface of a solid electrolyte membrane can effectively isolate the electrolyte and the electrode, reduce side reactions at the interface, and thus improve the performance and service life of the battery. The amount of electrolyte absorbed can be controlled by adjusting the porosity and thickness of the "sponge" material with a porous structure; the amount of electrolyte extrusion can be controlled by adjusting the applied pressure, so that the electrolyte seeps out of the "sponge" material, thereby forming a good contact between the electrolyte and the electrode, while not increasing the resistance of the electrode, effectively improving the performance of the battery.

[0056] Furthermore, if the thickness of the "sponge" material with a porous structure is less than 5μm or its porosity is less than 15%, the storage capacity of the "sponge" material for electrolyte is limited, so that the electrolyte content that can be absorbed is significantly reduced. This insufficient amount of electrolyte is difficult to fully infiltrate the surface of the electrode and the electrolyte membrane, resulting in a limited ion conduction path, which in turn affects the battery performance;

[0057] If the thickness of the "sponge" material with a porous structure is greater than 200 μm or the porosity is greater than 70%, there will be a large amount of space inside the "sponge" material that is not effectively utilized. Although these spaces can store electrolytes, most of the electrolytes may not effectively participate in the ion transport process during the operation of the battery, thereby reducing the energy efficiency and economy of the battery and causing a waste of electrolytes.

[0058] If the pressure applied to the saturated "sponge" material is less than 0.2MPa, it is impossible to ensure that the electrolyte in the "sponge" can be evenly and effectively distributed on the electrolyte surface. This uneven electrolyte distribution will cause the internal resistance of the battery to increase, affecting the uniform transmission of current and thus reducing the overall performance of the battery.

[0059] If the pressure applied to the saturated "sponge" material is greater than 2MPa, an excessive compression effect may occur, forcing the "sponge" to release too much electrolyte. This excessive release of electrolyte not only causes a waste of resources, but may also cause changes in the internal structure of the battery, such as the shedding of electrode materials or damage to the electrolyte membrane, thus posing a threat to the safety and life of the battery.

[0060] As an optional embodiment of the present invention, the "sponge" material with a porous structure includes one of polyurethane sponge, polyimide sponge, nickel foam or aluminum foam;

[0061] Specifically, the reason for using the materials mentioned above as the "sponge" materials is that these materials have high stability, will not react with the electrolyte, and will not react under high voltage / low voltage, and have no effect on battery performance; in addition, these materials have high thermal stability, with a thermal decomposition temperature higher than 350°C, and the battery has high safety.

[0062] And / or, the solid electrolyte is an inorganic solid electrolyte, and the inorganic solid electrolyte is a sulfide solid electrolyte;

[0063] Preferably, the sulfide solid electrolyte is LiPSCl5.

[0064] As an optional embodiment of the present invention, the electrolyte is an organic lithium salt electrolyte;

[0065] Preferably, the organic lithium salt electrolyte comprises an organic lithium salt and a solvent;

[0066] Preferably, the concentration of the organic lithium salt electrolyte is greater than 1 mol / L;

[0067] Preferably, the organic lithium salt includes one or more of N-methyl-N-butylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, bis(trifluoromethanesulfonyl)imide lithium, trifluoromethanesulfonate lithium, and tris(trifluoromethylsulfonyl)imide lithium;

[0068] Preferably, the solvent includes one or more of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.

[0069] As an optional embodiment of the present invention, the saturation state refers to a state in which a certain property or ability in an object or system reaches a maximum and cannot be increased or improved any further; the saturation state in the present invention refers to a state in which a "sponge" material with a porous structure can no longer absorb electrolyte.

[0070] According to a second aspect of the present invention, there is provided a method for preparing the "sponge" solid electrolyte as described above, comprising the following steps:

[0071] S1: pre-treating the "sponge" material with a porous structure;

[0072] S2: Soaking the pretreated "sponge" material in an electrolyte until it is saturated to obtain a saturated "sponge" material;

[0073] S3: Cover the saturated "sponge" material on both sides of the solid electrolyte to obtain a "sponge" solid electrolyte.

[0074] As an optional embodiment of the present invention, in step S1, the pretreatment includes selecting the porosity and thickness of the "sponge" material with a porous structure, and cutting it into the same size as the solid electrolyte.

[0075] As an optional embodiment of the present invention, in step S2, the saturated state is a state in which the pretreated "sponge" material can no longer absorb the electrolyte.

[0076] As an optional embodiment of the present invention, in step S3, the solid electrolyte is prepared into a membrane by a dry method, and is pressed at a pressure of 400 MPa when used, so that the interior of the solid electrolyte membrane is more dense, has no pores, and cannot penetrate the electrolyte.

[0077] According to the third aspect of the present invention, there is provided an application of a "sponge" solid electrolyte as described above or an application of a "sponge" solid electrolyte prepared by the preparation method of the "sponge" solid electrolyte as described above, which can be used to be assembled with positive and negative electrode sheets in a solid-state battery mold to form a solid-state battery.

[0078] Specifically, during the assembly process, the mass of the positive and negative electrodes may exert pressure on the saturated "sponge" solid electrolyte respectively, but this pressure will not cause the electrolyte to overflow from the saturated "sponge". Therefore, after the battery is assembled, when the battery is tested, pressure is applied to the "sponge" solid electrolyte through the pressure sensor in the solid-state battery mold to deform the "sponge" solid electrolyte, thereby causing the electrolyte to overflow from the saturated "sponge" and infiltrate the surfaces of the positive and negative electrodes, thereby improving the interface contact.

[0079] As an optional embodiment of the present invention, in the solid-state battery, Figure 1 As shown, from top to bottom are: negative electrode current collector 1, negative electrode active material layer 2, saturated "sponge" material layer 3, inorganic solid electrolyte layer 4, saturated "sponge" material layer 3, positive electrode active material layer 5 and positive electrode current collector 6.

[0080] Among them, the negative electrode current collector 1 and the negative electrode active material layer 2 coated on the surface of the negative electrode current collector constitute a negative electrode sheet;

[0081] The positive electrode current collector 6 and the positive electrode active material layer 5 coated on the surface of the positive electrode current collector constitute a positive electrode sheet;

[0082] The inorganic solid electrolyte layer 4 and the saturated “sponge” material layers 3 on both sides of the inorganic solid electrolyte layer 4 constitute a “sponge” solid electrolyte.

[0083] As an optional embodiment of the present invention, the positive electrode current collector includes aluminum foil, carbon material, etc.;

[0084] The positive electrode active material layer is a high-nickel NCM ternary material.

[0085] As an optional embodiment of the present invention, the negative electrode current collector includes copper foil, titanium foil, nickel foil, stainless steel, etc.;

[0086] The negative electrode active material layer is made of silicon-carbon Si-C material.

[0087] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.

[0088] Example 1

[0089] Preparation of sulfide (LiPSCl5) solid electrolyte:

[0090] The membrane is prepared by a dry method, with a diameter of φ19 mm and a thickness of 65 μm. It is pressed under a pressure of 400 MPa during use, making the interior of the solid electrolyte membrane more dense, without pores, and unable to penetrate the electrolyte.

[0091] Preparation of "sponge" solid electrolyte:

[0092] (1) Select a polyurethane "sponge" material (a "sponge" material with a porous structure) with a porosity of 40% and cut it into a size of φ19 mm and a thickness of 25 μm so that it can cover the surface of the sulfide solid electrolyte membrane;

[0093] (2) Soaking the cut polyurethane sponge in an electrolyte of N-methyl-N-butylpyrrolidine bis(trifluoromethanesulfonyl)imide salt for 5 minutes, and leaving it for later use after it is filled with the electrolyte to saturation;

[0094] Wherein, N-methyl-N-butylpyrrolidine bis(trifluoromethanesulfonyl)imide salt is placed in ethylene carbonate to prepare an organic lithium salt electrolyte with a concentration of 2 mol / L;

[0095] (3) Covering the soaked polyurethane sponge (saturated "sponge" material) on both sides of the sulfide solid electrolyte membrane to obtain a "sponge" solid electrolyte.

[0096] Preparation of fully sealed mold solid-state batteries:

[0097] The "sponge" solid electrolyte, the positive electrode sheet and the negative electrode sheet obtained above are assembled in a solid-state battery mold, and a pressure of 0.4MPa is applied through a pressure sensor to deform the "sponge" solid electrolyte, causing the electrolyte to seep out. The seeped electrolyte can infiltrate the surface of the electrode sheet and improve the contact between the solid electrolyte and the electrode;

[0098] Preparation of the positive electrode: High nickel NCM ternary material and PVDF, SP, CNT were mixed evenly in a mass ratio of 96.5:2.0:1.0:0.5 and evenly coated on a 13 μm carbon-coated aluminum foil to obtain a surface density of 190 mg / 10 cm 2 The positive electrode;

[0099] Preparation of negative electrode sheet: Silicon carbon, SP, CMC, and SBR were mixed evenly in a mass ratio of 94:2:1.5:2.5, and coated evenly on a 6μm copper foil to obtain a surface density of 90mg / 10cm 2 The negative electrode;

[0100] In the solid-state battery mold, from top to bottom, they are: the negative electrode sheet, the "sponge" solid electrolyte and the positive electrode sheet assembled into a fully sealed mold solid-state battery.

[0101] Embodiment 2-8

[0102] The preparation methods in Examples 2-8 are the same as those in Example 1. The technical parameters and operations different from those in Example 1 are shown in Table 1.

[0103] Comparative Example 1

[0104] The sulfide (LiPSCl5) solid electrolyte, the positive electrode sheet prepared in Example 1, and the negative electrode sheet are directly assembled in a solid-state battery mold without applying pressure and adding electrolyte, as shown in Table 1.

[0105] Comparative Example 2

[0106] The sulfide (LiPSCl5) solid electrolyte, the positive electrode sheet prepared in Example 1, and the negative electrode sheet were directly assembled in a solid-state battery mold, a pressure of 5 MPa was applied, and no electrolyte was added, as shown in Table 1.

[0107] Comparative Example 3

[0108] The sulfide (LiPSCl5) solid electrolyte, the positive electrode sheet prepared in Example 1, and the negative electrode sheet were directly assembled in a solid-state battery mold, a pressure of 0.4 MPa was applied, and 2 drops of the electrolyte in Example 1 were added, as shown in Table 1.

[0109] Comparative Examples 4-7

[0110] The preparation methods in Comparative Examples 4-7 are the same as those in Example 1. The technical parameters and operations different from those in Example 1 are shown in Table 1.

[0111] Table 1

[0112]

[0113] Performance Testing

[0114] The performance test of the fully sealed mold solid-state battery prepared in the above-mentioned embodiment and comparative example specifically includes:

[0115] Battery capacity retention rate

[0116] The capacity retention rate refers to the ratio of the discharge capacity of the battery to the initial discharge capacity after a certain period of time or a certain number of cycles, and is usually expressed as a percentage. The prepared battery is subjected to a battery capacity retention rate test. The specific test method includes the following steps:

[0117] 1) Initial discharge capacity test: First, perform the initial charge and discharge test at 0.1C in the voltage range of 2.5-4.2V to obtain the initial discharge capacity of the battery;

[0118] 2) Cycle: Charge and discharge test at 0.2C charge and 0.2C discharge, initial discharge capacity C0;

[0119] 3) Discharge test again: After the 30-cycle test cycle is completed, the battery is charged at 0.2C and discharged at 0.2C again to obtain the discharge capacity C1 at this time;

[0120] Calculate the capacity retention rate: According to the definition of capacity retention rate, that is, the ratio of C1 to C0, the capacity retention rate of the battery is calculated;

[0121] The higher the capacity retention rate, the more stable the battery performance and the longer its service life.

[0122] Coulombic efficiency of battery

[0123] The coulombic efficiency of a battery refers to the ratio of the output charge to the input charge during the charge and discharge process of the battery, usually expressed as a percentage. The prepared battery is subjected to a coulombic efficiency test. The specific test method includes the following steps:

[0124] 1) Preparation stage: Place the battery in a thermostat and connect the battery and the test equipment using a four-wire method. Set the thermostat temperature to 35°C to simulate the temperature conditions of the actual working environment.

[0125] 2) Connect the test equipment: Make sure the battery is properly connected to the test equipment for subsequent charge and discharge tests;

[0126] 3) Charge and discharge test: Perform charge and discharge test on the battery according to the requirements of the test equipment. During the charging process, record the input charge of the battery; during the discharging process, record the output charge of the battery;

[0127] The value of the coulombic efficiency was calculated based on the ratio of the recorded output charge to the input charge.

[0128] The higher the coulombic efficiency, the smaller the charge loss of the battery during the charging and discharging process, and the better the performance.

[0129] The above test results are shown in Table 2:

[0130] Table 2

[0131]

[0132]

[0133] As shown in Comparative Example 1 in Table 2, in the solid-state battery, when no sponge material or electrolyte is added and the applied pressure is 0, the interface contact between the electrode and the electrolyte membrane is poor, the battery impedance is large, the battery performance cannot be normally exerted, and the battery cycle performance is poor.

[0134] As shown in Comparative Example 2 in Table 2, in a solid-state battery, when no "sponge" material is attached to both sides of the solid electrolyte membrane, a greater pressure is required to improve the interface contact with the electrodes.

[0135] As shown in Comparative Example 3 in Table 2, in a solid-state battery, directly adding electrolyte at the interface will cause uneven distribution of the electrolyte at the interface and poor battery performance.

[0136] As shown in Comparative Example 4 and Example 3 in Table 2, in solid-state batteries, when the porosity of the "sponge" material is large, the amount of electrolyte used will increase, and the ability of the pores to bind the electrolyte will weaken, resulting in easy loss of electrolyte during the cycle process and reduced battery cycle performance.

[0137] As shown in Comparative Example 5 in Table 2, in a solid-state battery, when the thickness of the "sponge" material is large, there is a large amount of ineffectively utilized space inside the "sponge" material, so that most of the electrolyte does not effectively participate in the ion transport process, thereby reducing the battery's energy efficiency and battery cycle performance, and causing waste of electrolyte.

[0138] As shown in Comparative Example 6 in Table 2, in solid-state batteries, when the pressure applied to the "sponge" material is large, an excessive compression effect occurs, forcing the "sponge" to release too much electrolyte. This excessive release of electrolyte not only causes a waste of resources, but may also cause changes in the internal structure of the battery, posing a threat to the safety and life of the battery.

[0139] As shown in Comparative Example 7 in Table 2, in the solid-state battery, when the "sponge" material is in an unsaturated state of absorbing the electrolyte, when the applied pressure is 0.4 MPa, the electrolyte cannot overflow from the "sponge" material, the interface contact between the electrode and the electrolyte membrane is poor, the battery impedance is large, the battery performance cannot be normally exerted, and the battery cycle performance is poor.

[0140] In summary, the use of a "sponge" that absorbs electrolyte has little effect on the use of sponge materials, and does not require too much pressure to improve the interface contact of a single cell, thereby reducing energy loss during battery manufacturing. Porosity and material thickness affect the amount of electrolyte adsorbed. Too small a porosity and a thin material thickness result in less electrolyte adsorption, which fails to fully wet the surface of the electrode and electrolyte membrane, affecting battery performance. Excessively large porosity and thicker "sponge" materials absorb more electrolyte, which results in a partial waste of electrolyte.

[0141] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A "sponge" solid electrolyte, characterized in that: It includes a solid electrolyte and a saturated "sponge" material covering both sides of the solid electrolyte; Wherein, the saturated "sponge" material is obtained by absorbing the electrolyte to a saturated state through the "sponge" material having a porous structure; The saturated "sponge" material can undergo elastic deformation under a certain pressure, so that the electrolyte seeps out of the "sponge" material.

2. The "sponge" solid electrolyte according to claim 1, characterized in that: The thickness of the "sponge" material with a porous structure is 5 to 200 μm, preferably 25 μm; And / or, the porosity of the "sponge" material having a porous structure is 15% to 70%, preferably 40%; And / or, the pressure applied to the saturated "sponge" is in the range of 0.2 to 2 MPa, preferably 0.4 MPa.

3. The "sponge" solid electrolyte according to claim 1, characterized in that: The "sponge" material with a porous structure includes one of polyurethane sponge, polyimide sponge, nickel foam or aluminum foam; And / or, the solid electrolyte is an inorganic solid electrolyte; The inorganic solid electrolyte is a sulfide solid electrolyte; The sulfide solid electrolyte is LiPSCl5.

4. The "sponge" solid electrolyte according to claim 1, characterized in that: The electrolyte is an organic lithium salt electrolyte; The organic lithium salt electrolyte comprises an organic lithium salt and a solvent; The concentration of the organic lithium salt electrolyte is greater than 1 mol / L; The organic lithium salts include N-methyl-N-butylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, bis(trifluoromethanesulfonyl)imide lithium, lithium trifluoromethanesulfonate, and lithium tris(trifluoromethylsulfonyl)imide; The solvent includes one or more of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.

5. The "sponge" solid electrolyte according to claim 1, characterized in that: The saturated state refers to a state in which the "sponge" material with a porous structure can no longer absorb the electrolyte.

6. A method for preparing a "sponge" solid electrolyte as claimed in any one of claims 1 to 5, characterized in that: The steps include: S1: pre-treating the "sponge" material with a porous structure; S2: Soaking the pretreated "sponge" material in an electrolyte until it is saturated to obtain a saturated "sponge" material; S3: Cover the saturated "sponge" material on both sides of the solid electrolyte to obtain a "sponge" solid electrolyte.

7. The method for preparing the "sponge" solid electrolyte according to claim 6, characterized in that: In step S1, the pretreatment includes selecting the porosity and thickness of the "sponge" material with a porous structure, and cutting it into the same size as the solid electrolyte.

8. A "sponge" solid electrolyte prepared by the preparation method of the "sponge" solid electrolyte as claimed in any one of claims 6 to 7 or a use of the "sponge" solid electrolyte as claimed in any one of claims 1 to 5, characterized in that: It can be used to assemble with positive electrode sheets and negative electrode sheets in a solid-state battery mold to form a solid-state battery.

9. The use according to claim 8, characterized in that: In the solid-state battery, from top to bottom, there are: negative electrode current collector, negative electrode active material layer, saturated "sponge" material layer, inorganic solid electrolyte layer, saturated "sponge" material layer, positive electrode active material layer and positive electrode current collector; Wherein, the negative electrode current collector and the negative electrode active material layer coated on the surface of the negative electrode current collector constitute the negative electrode sheet; The positive electrode current collector and the positive electrode active material layer coated on the surface of the positive electrode current collector constitute a positive electrode sheet; The inorganic solid electrolyte layer and the saturated "sponge" material layers on both sides of the inorganic solid electrolyte layer constitute a "sponge" solid electrolyte.

10. The use according to claim 9, characterized in that: The positive electrode current collector comprises aluminum foil or carbon material; The positive electrode active material layer is a high-nickel NCM ternary material; And / or, the negative electrode current collector comprises one of copper foil, titanium foil, nickel foil and stainless steel; The negative electrode active material layer is made of silicon-carbon material.

Citation Information

Patent Citations

  • Compressible supercapacitor based on porous sponge structures

    CN107705996A

  • Preparation method of integrated lithium air battery based on composite solid electrolyte

    CN115692952A

  • Lithium cell separator with sponge material layer

    DE102017211412A1

  • Multi layer ceramic battery

    US8304115B1

  • Delocalized lithium ion FLUX by solid-state electrolyte composites coupled with 3D porous nanostructures for highly stable lithium metal batteries

    WO2024030448A1